An optical survey for space debris on highly eccentric and inclined MEO orbits. Issue 1 (1st January 2017) - Silha, J.; Schildknecht, T.; Hinze, A.; Flohrer, T.; Vananti, A.
Highlights: Development of a survey and follow-up strategy for searching space debris objects in highly-eccentric MEO orbits. Acquisition of an optical survey of Molniya-type orbits with ESA OGS telescope. Detection of 15 correlated and 30 un-correlated Molniya objects. Description of dynamical and physical parameters of newly discovered objects. Raw estimate of the size of non-cataloged Molniya population. Abstract: Optical surveys for space debris in high-altitude orbits have been conducted since more than ten years. Originally these efforts concentrated mainly on the geostationary region (GEO). Corresponding observation strategies, processing techniques and cataloguing approaches have been developed and successfully applied. The ESA GEO surveys, e.g., resulted in the detection of a significant population of small-size debris and later in the discovery of high area-to-mass ratio objects in GEO-like orbits. Comparably less experience (both, in terms of practical observation and strategy definition) is available for eccentric orbits that (at least partly) are in the MEO region, in particular for the Molniya-type orbits. Different survey and follow-up strategies for searching space debris objects in highly-eccentric MEO orbits, and to acquire orbits which are sufficiently accurate to catalog such objects and to maintain their orbits over longer time spans were developed. Simulations were performed to compare the performance of different survey and cataloguing strategies. Eventually, optical observations were conducted in the framework of an ESA study using ESA's Space Debris Telescope (ESASDT) the 1-m Zeiss telescope located at the Optical Ground Station (OGS) at the Teide Observatory at Tenerife, Spain. Thirteen nights of surveys of Molniya-type orbits were performed between January and August 2013. Eventually 255 surveys were performed during these thirteen nights corresponding to about 47 h of observations. In total 30 uncorrelated faint objects were discovered. On average one uncorrelated object was found every 100 min of observations. Some of these objects show a considerable brightness variation and have a high area-to-mass ratio as determined in the orbit estimation process.